2004
DOI: 10.1016/j.otohns.2004.06.281
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologic Markers for Early Diagnosis of Turner Syndrome

Abstract: Objective-To identify and characterize otolaryngologic markers for the early diagnosis of Turner Syndrome (TS).Study Design-Prospective cohort survey. Setting: Clinical Center of the National Institutes of Health (NIH).Patients: Ninety-one females, 7 -61 years old (average = 28.7 y), enrolled in a multidisciplinary study of karyotype-phenotype correlations in TS. Main Outcome Measures:Age at diagnosis, X chromosome karyotype, history of chronic or recurrent otitis media (OM), sensorineural hearing loss (SNHL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…22 According to several studies, the incidence of SNHL among different age groups in TS patients varies from 9% to 83% (Table 1). 12,20 Our study showed a relative low incidence (17.4%, age range: 5e34 years), similar to the incidence (19%, age range: 6e25 years) reported by Serra and others. 11 The fact that most of our patients were teenagers (mean age 17.3 years) likely explains a lower incidence of SNHL when compared with other studies involving young and middle-age women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…22 According to several studies, the incidence of SNHL among different age groups in TS patients varies from 9% to 83% (Table 1). 12,20 Our study showed a relative low incidence (17.4%, age range: 5e34 years), similar to the incidence (19%, age range: 6e25 years) reported by Serra and others. 11 The fact that most of our patients were teenagers (mean age 17.3 years) likely explains a lower incidence of SNHL when compared with other studies involving young and middle-age women.…”
Section: Discussionsupporting
confidence: 89%
“…2e20 The reported incidence of recurrent OM varies from 12% to 91%, 16,20 although the exact cause remains unknown. According to a large-scale population study (200 cases), approximately 50% of TS patients suffer from hearing loss with conductive, sensorineural, or mixed pattern.…”
Section: Introductionmentioning
confidence: 99%
“…CTscanning (Dhooge et al, 2005) could not demonstrate anomalies of the inner ear or vestibular system responsible for the hearing loss. Only one study showed hypoplastic lateral semicircular canals by CT-scanning in two TS patients with SNHL (Makishima et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many TS patients have an abnormal craniofacial morphology. A retarded development of the cranial skeleton, an unusual downward slope of the external auditory canal and palatal anomalies such as a high arched palate are frequently seen (Anderson et al, 1969;Filipsson et al, 1965;Gungor et al, 2000;Makishima et al, 2009;Midtbo et al, 1996;Sculerati et al, 1990). These findings have impact on the Eustachian tube function causing recurrent middle ear infections.…”
Section: Introductionmentioning
confidence: 99%